Biomechanical Comparison of Four Different Atlantoaxial Posterior Fixation Constructs in Adults: A Finite Element Study. Issue 15 (1st August 2018) - Chun, Dong Hyun; Yoon, Do Heum; Kim, Keung Nyun; Yi, Seong; Shin, Dong Ah; Ha, Yoon
Abstract : Study Design: Finite element analysis. Objective: To compare the biomechanical stability imparted to the C1 and C2 vertebrae by the transarticular (TA), C1 lateral mass (LM)-C2 pedicle (PS), C1LM-C2 pars, and C1LM-C2 translaminar (TL) screw fixation techniques. Summary of Background Data: Cadaveric biomechanical studies of several atlantoaxial posterior fixation techniques have been performed, showing significant heterogeneity in biomechanical properties among the studies. Methods: From computed tomography images, a nonlinear intact three-dimensional C1–2 finite element model was developed and validated. Four finite element models were reconstructed from different C1–2 fixation techniques. The range of motion (ROM) and maximum von Misses stresses for the four screw techniques were compared under flexion, extension, lateral bending, and axial rotation. Results: C1LM-C2PS showed the greatest decrease in ROM with flexion/extension and lateral bending. C1–2TA and C1LM-C2 pars showed less ROM reduction than the other techniques, in flexion/extension. C1LM-C2TL showed the least decrease in ROM during axial rotation. For C1–2TA, the maximum stress was in the C1–2 joint region. In the C1LM-C2PS, the C1 rod head, C2 pars screw, and C2TL screw were stressed at the C2 rod head. The maximal von Mises stress on the C1–2TA at the C1–2 joint site was the highest at flexion/extension, whereas the C1LM-C2PS had the lowest stress on the screw at flexion/extension and lateral bending. The C1LM-C2TL showed the highest stress in axial rotation and lateral bending. Conclusion: In this study, C1LM-C2PS fixation was the most stable technique. If surgeons have to use other fixation methods besides the C2 pedicle screw, they need to be aware that additional fixation or postoperative immobilization may be required to achieve ROM restriction. Careful observation at the maximum stress site on the screw including screw loosening, screw-bone interface disruption or screw fracture will be necessary during follow-up imaging examinations (x-ray and computed tomography scan) after atlantoaxial fixation. Level of Evidence: N/A Abstract : Supplemental Digital Content is available in the text